PENGARUH PROMOSI ONLINE DAN PERILAKU KONSUMEN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN AYAM PEDAGING - Herman Sjahruddin; Aulia Qarinah; Nurlaely Razak; Poppy Nahdia Syahrani Pascawati (Jurnal Ilmu Manajemen, 2022)
A micro business is expected to be one of the economic activities that can support the national economy and become a pillar of the nation's economy. One of the rapidly growing micro units in Makassar City is Cahaya Huspi. This study aims to explore the two determinants of purchasing decisions using 97 responses from 161 distributed questionnaires. Data is analysed using multiple regression analysis. It provides evidence that intense online promotions, indicated by the high frequency of advertising, sales promotions, and direct marketing, are the reasons consumers make purchases, as indicated by the high response to the product stability, buying habits and purchase speed. This finding is different from consumer behaviour measured by cultural, social, personal, and psychological factors that are not proven as determinants of purchasing decisions. This study implies the importance of using online promotion in marketing communications for micro-enterprises because of its convenience, low cost, and broad reach.